2020
DOI: 10.47236/2594-7036.2021.v5.i1.100-117p
|View full text |Cite
|
Sign up to set email alerts
|

A época de semeadura na produção de sementes de soja em condições de várzea tropical

Abstract: A época de semeadura é considerada fator de maior influência cultural na soja, no entanto, poucos são os trabalhos realizados em condições de várzea tropical que avaliam o seu efeito. O objetivo deste trabalho foi avaliar o efeito das épocas de semeadura em quatro cultivares de soja em condições de várzea tropical. Os ensaios de campo foram instalados em 13/maio, 23/maio e 03/junho de 2020 e em cada um foram utilizados quatro cultivares de soja (GMR = 8,1; 8,6; 7,4 e; 7,1) em delineamento de blocos ao acaso e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…These results agree with those obtained by Barbosa et al (2011), Finoto et al (2017), and Carvalho et al (2021, who also observed the effects of high temperatures and water reductions in the increase of oil content in soybean grains. Naoe et al (2020), also had about the isolated and/or associated effect of low water availability and high temperatures on the oil content.…”
Section: Resultssupporting
confidence: 93%
“…These results agree with those obtained by Barbosa et al (2011), Finoto et al (2017), and Carvalho et al (2021, who also observed the effects of high temperatures and water reductions in the increase of oil content in soybean grains. Naoe et al (2020), also had about the isolated and/or associated effect of low water availability and high temperatures on the oil content.…”
Section: Resultssupporting
confidence: 93%
“…Além do efeito ambiental e manejo, as características genéticas de cada cultivar também podem influenciar na presença de sementes esverdeadas (Pádua et al, 2009;Rangel et al, 2011;Bordignon et al, 2017;Carvalho et al, 2021). Carvalho et al (2021), usaram diferentes cultivares plantadas em diferentes épocas do ano e constataram que algumas cultivares eram mais susceptíveis a desenvolver sementes esverdeadas.…”
Section: Fatores Que Influenciam a Produção De Sementes Esverdeadasunclassified
“…Além do efeito ambiental e manejo, as características genéticas de cada cultivar também podem influenciar na presença de sementes esverdeadas (Pádua et al, 2009;Rangel et al, 2011;Bordignon et al, 2017;Carvalho et al, 2021). Carvalho et al (2021), usaram diferentes cultivares plantadas em diferentes épocas do ano e constataram que algumas cultivares eram mais susceptíveis a desenvolver sementes esverdeadas. Pádua et al (2009) realizaram um trabalho com quatro cultivares e três condições de disponibilidade hídrica, verificando que a cultivar Robusta apresentou maior presença de clorofila em ambiente mais estressante do que as demais cultivares (Gráfico 2).…”
Section: Fatores Que Influenciam a Produção De Sementes Esverdeadasunclassified
“…In Brazil, soybeans have immense economic significance, as they serve as a primary product of national agriculture and reinforce the country's position as an essential participant in the global agricultural market. This, in turn, allows more significant influence in the domain of global commodity trade (HIRAKURI; LAZZAROTTO, 2014;CARVALHO et al, 2021). For the 2020/21 harvest, the estimated national grain production was 252.3 million tons.…”
Section: Introductionmentioning
confidence: 99%